Entwicklung und Validierung des Stapesplasty Outcome Test 25 (SPOT-25) - Lailach, Susen; Baumann, Ingo; Walter, Hannah; Praetorius, Mark (HNO, 2017)
Background: Otosclerosis affects health-related quality of life (HRQOL). Until now, measurements have only been performed using audiometric data or non-validated quality of life questionnaires.ObjectiveThe objective of this study was to develop the first validated disease-specific HRQOL measuring instrument to determine HRQOL in otosclerosis. Materials and methods: After sequential analysis and item reduction of the initial Stapesplasty Outcome Test 47 (SPOT-47), the SPOT-25 was validated prospectively on 52 otosclerosis patients undergoing stapes surgery. In addition to the overall score, four subscores were defined (hearing function, tinnitus, social restrictions, mental condition). Results: The SPOT-25 showed a high internal consistency (Cronbach’s α > 0.7), allowed discrimination between otosclerosis patients and healthy subjects, and demonstrated acceptable test-retest reliability (r = 0.85). After stapes surgery, the HRQOL improved significantly. The responsiveness was high. Conclusion: The SPOT-25 is the first validated disease-specific instrument for HRQOL measurement in otosclerosis patients. It should be used routinely for quality control.
Gesehen am 25.10.2018